2016
DOI: 10.1016/j.devcel.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Signaling Is Required for Glucose-Induced Insulin Secretion

Abstract: Summary Insulin secretion by pancreatic islet β-cells is critical for glucose homeostasis, and a blunted β-cell secretory response is an early deficit in type 2 diabetes. Here, we uncover a regulatory mechanism by which glucose recruits vascular-derived neurotrophins to control insulin secretion. Nerve Growth Factor (NGF), a classical trophic factor for nerve cells, is expressed in pancreatic vasculature while its TrkA receptor is localized to islet β-cells. High glucose rapidly enhances NGF secretion, and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 77 publications
6
50
0
Order By: Relevance
“…In that study, blockade of NGF-TrkA signaling in mice using chemical genetics and pancreas-specific TrkA knockout impaired insulin secretion and glucose tolerance. Glucose also induced TrkA phosphorylation (21). In several studies of NGF action on islets including those discussed here and our previous work (49), pharmacological concentrations of NGF were used, up to 50 times higher than the concentration of BDNF needed to induce ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In that study, blockade of NGF-TrkA signaling in mice using chemical genetics and pancreas-specific TrkA knockout impaired insulin secretion and glucose tolerance. Glucose also induced TrkA phosphorylation (21). In several studies of NGF action on islets including those discussed here and our previous work (49), pharmacological concentrations of NGF were used, up to 50 times higher than the concentration of BDNF needed to induce ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 91%
“…NGF and its receptor TrkA have been linked to β cells for a number of years (18,20,21,49,55). A recent study concluded that NGF and TrkA have a critical role in β cell function in mice and in isolated islets from mice and humans (21). In that study, blockade of NGF-TrkA signaling in mice using chemical genetics and pancreas-specific TrkA knockout impaired insulin secretion and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, pericytes produce components of the extracellular matrix that promote beta cell proliferation, a process that is hindered when pericytes are depleted. Furthermore, it is proposed that pericytes produce growth factors required for glucose‐stimulated insulin exocytosis . In the absence of these growth factors, beta cells dedifferentiate into an immature form and lose the ability to tailor insulin secretion to blood glucose concentration .…”
Section: Pericytes and Capillary Blood Flowmentioning
confidence: 99%